The association between medical diseases and orofacial abscess: A retrospective, hospital-based study - Hassan Abed; Majed Obaid; Khalid Al-Johani (Saudi Dental Journal)
Objective: This study aimed to identify the most commonly reported medical diseases among dental patients and to assess its association with the development of the orofacial abscess. Methods: The medical records (n = 3164) of dental patients who visited the dental hospital at Umm-Al-Qura University (Makkah, Saudi Arabia) were reviewed. Demographic characteristics of eligible patients were collected. Medical diseases were collected as reported by the patients in the medical records. The International Classification of Diseases (ICD-10) was used to classify the reported medical diseases. Simple descriptive statistics were used to define the characteristics of the study variables through a form of counts and percentages. Multivariable logistic regression analysis was carried out to find out the significant predictors of orofacial abscess. Results: Upon reviewing 3164 medical records, almost half of the patients had medical diseases (n = 1543, 49%). The mean age of the cohort was 30.3 (SD = 16.43). Diabetes mellitus (n = 316, 20%) and hypertension (n = 210, 14%) were the most common reported medical diseases. Male patients reported having more medical diseases compared to the female. Hypertension was found to be significantly high among female patients (X2 = 3.167, P-value < 0.001). Multivariable logistic regression analysis indicated that the female gender is significantly associated with the development of orofacial abscess after adjustment for age and vascular risk factors (i.e., hypertension) (B = 1.26, S.E. = 0.57, OR = 3.54, 95%CI = 1.13 to 11.40, P-value = 0.028). Conclusion: Dentists should be aware that diabetes mellitus and hypertension are prevalent among patients visiting dental services. The female gender has a higher association of developing orofacial abscess than male. Within the limitation of this study in a single study center with few patients having orofacial abscess, this study found no association between medical diseases and the development of orofacial abscess.